EFEKTIVITAS MENGEKSPLORASI KONSEP DAN PROSES FISIKA PADA MATERI SIKLUS AIR - Milania Suwu; Djeli Alvi Tulandi; Jimmy Lolowang (Charm Sains: Jurnal Pendidikan Fisika, 2023)
Explorative learning about the concepts and processes of physics in the water cycle material is an example of a physics learning process by utilizing the natural surroundings as learning objects. The purpose of this study was to determine the effectiveness of exploring the concepts and physical processes contained in the water cycle material. This study used the one group pretest-posttest design pre-experimental method. This research was conducted through three stages. The first stage is to provide a pretest to measure students' initial abilities. The second stage is giving treatment through exploratory learning and the third stage is giving a posttest as a learning evaluation. The research subjects were students in semester VI of Physics Education, Manado State University 2022/2023. Retrieval of data in the form of tests in the form of observation tables/exploration formats. After obtaining the data, the research results were statistically processed using the SPSS 22.0 for windows application. The average pretest result was 48.43 which increased to 81.12 on the average posttest result. Obtaining N-Gain Scores from each student, there were 9 students in the high N-Gain category with a percentage of 56.25% and 2 students were in the medium N-Gain category with a percentage of 43.75%. The results of the average percentage of N-Gain from 16 students is 63.43%, which is in the quite effective category. Based on the explanation above, it can be concluded that exploratory learning is quite effective for analyzing concepts and physical processes in the water cycle material.